Elemental Mapping and Quantities in Different Soybean Seed Colors Using Micro X-Ray Fluorescence and Their Correlations with Germination - K. Wibisono; W. Nurcholis (National Research and Innovation Agency, 2023)
Micro X-ray fluorescence (Î¼-XRF) possesses a powerful analytical technique able to detect macro- and micro-elements. Each plant variety has a unique elemental composition and important role in the germination process. The aims of this study were to (1) map the elements and quantities in the soybean seed coat and endosperm, (2) investigate how the various elements might mediate the inter-relationship or correlation between elements within soybean seed genotypes with different seed coat colors, and (3) investigate that the targeted morphological characteristics especially in germination would be affected by seed elements. A Î¼-XRF technique was used for the elemental analysis and quantification. Three genotypes of Indonesian soybean were used in this study: greenish, black, and yellowish. In this study, we found that the silicon (Si) and magnesium (Mg) elements have a significant correlation. The high quantity of Si element in the embryo axis has a positive correlation with root length. The high quantity of Mg element which is evenly distributed on the endosperm has a positive correlation with normal germination. Si and Mg elements in the seeds have a negative correlation with imbibition water absorption. Based on the comparison between the three genotypes, the black genotype was superior in terms of germination and higher Si and Mg elements. Thus, the Si and Mg elements can be used as a reference in determining superiority of genotypes at the germination stage.